Moral Values Implementation Through Nussa Rara Animated Series: Penerapan Nilai-Nilai Moral Melalui Serial Animasi Nussa Rara - Adinda Try Hidayah; Nurdyansyah Nurdyansyah (Academia Open, 2025)
General Background: Character education has become a central concern in elementary education due to increasing moral degradation among students in school environments. Specific Background: At SDN Cemeng Bakalan 1 Sidoarjo, observations aligned with national child protection reports indicate declining social character reflected in impolite communication, conflicts, and low empathy among students. Knowledge Gap: Previous studies primarily examined the moral messages contained in the Nussa and Rara animated film, yet limited research has analyzed supporting and inhibiting factors in the real implementation of these values within school contexts. Aims: This study aims to analyze the moral values presented in selected Nussa and Rara episodes and to examine supporting and inhibiting factors in their implementation for developing children’s social character. Results: Using a qualitative descriptive approach with observation, interviews, and documentation analyzed through the Miles and Huberman model, findings reveal that episodes such as Jangan Kalah Sama Setan, Adab Menasihati, Maaf, and Tolong dan Terima Kasih convey values of empathy, tolerance, politeness, forgiveness, and cooperation. Positive behavioral changes were observed gradually among students, supported by engaging visuals, relatable storylines, and student enthusiasm, while limited parental involvement and unsupportive social environments emerged as barriers. Novelty: The study highlights implementation dynamics beyond content analysis by identifying contextual facilitators and constraints. Implications: Findings suggest that animated Islamic media can support social character formation when reinforced by parental guidance and positive school environments. Keywords: Moral Values, Social Character, Animated Film, Character Education, Elementary Students Key Findings Highlights: Selected episodes present concrete models of empathy, forgiveness, and polite communication in daily interactions. Gradual reduction in student conflict and increased cooperative behavior were observed after repeated screenings. Parental involvement and social environment conditions determine sustainability of character internalization.